CHEK2 1100DELC germline mutation: a frequency study in hereditary breast and colon cancer Brazilian families - Abud,Jamile (2012)
CONTEXT: CHEK2 encodes a cell cycle checkpoint kinase that plays an important role in the DNA damage repair pathway, activated mainly by ATM (Ataxia Telangiectasia Mutated) in response to double-stranded DNA breaks. A germline mutation in CHEK2, 1100delC, has been described as a low penetrance allele in a significant number of families with breast and colorectal cancer in certain countries and is also associated with increased risk of contralateral breast cancer in women previously affected by the disease. About 5%-10% of all breast and colorectal cancers are associated with hereditary predisposition and its recognition is of great importance for genetic counseling and cancer risk management. OBJECTIVES: Here, we have assessed the frequency of the CHEK2 1100delC mutation in the germline of 59 unrelated Brazilian individuals with clinical criteria for the hereditary breast and colorectal cancer syndrome. METHODS: A long-range PCR strategy followed by gene sequencing was used. RESULTS: The 1100delC mutation was encountered in the germline of one (1.7%) individual in this high risk cohort. This indicates that the CHEK2 1100delC is not commonly encountered in Brazilian families with multiple diagnoses of breast and colorectal cancer. CONCLUSION: These results should be confirmed in a larger series of families and further testing should be undertaken to investigate the molecular mechanisms underlying the hereditary breast and colorectal cancer phenotype.